Study of Lung Function Tests and ECG Changes in Subclinical Hypothyroid Female Subjects - Kanwal Abbas Bhatti, Noor Nabi Siyal, Altaf Hussain Memon, Ghulam Muhammad Phull, Hanozia Hassan, Mukhtiar Ahmed Abro, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To study changes in electrocardiogram AND pulmonary function tests in a group of women with newly diagnosed subclinical hypothyroidism. Methodology: The study was conducted on 30 women between the ages of 20 and 40 with subclinical hypothyroidism and compared to 30 age and gender-matched controls. The student's test was used to do statistical analysis in SPSS version 23. Results: A total of 30 women who had subclinical hypothyroidism and 30 healthy, age- and sex-matched controls were included. The mean±SD height of the controls was 152.9 ± 3.7 cm and that of SCH patients was 153.1 ± 4.08 cm. Height differences between the two groups were insignificant. The mean±SD weight of the controls was 51.9 ± 4.5 kg and that of SCH subjects was 53.2 ± 4.3 kg. Weight differences between the two groups were insignificant. The mean±SD BMI of the controls was 22.16 ± 1.64 kg/m2 and that of SCH subjects was 22.71 ± 1.99 kg/m2. BMI differences between the two groups were insignificant. Conclusion: Results have suggested that the changes will occur in spirometry and electrocardiogram, even in the subclinical state of hypothyroidism. Precautions can be taken at this stage to prevent progression to overt hypothyroidism.